N-traps and C-ancas in a lupus erythematosus-scleroderma overlap syndrome with vasculitis and panniculitis - Ana Maria Abreu Velez; Vickie M. Brown; Lyndsay Shipp; Bruce R. Smoller; Michael S. Howard (Our Dermatology Online, 2013)
Histologic vasculitis must be interpreted with caution, as there is considerable overlap in its clinical, histologic and immunologic presentations. Case report: A 42 year old woman presented with an plaque on the buttock that was tender to palpation, and had been present for six weeks. Physical examination revealed a large, erythematous plaque with focal areas of atrophy, pigmentation, small crusts, and small blisters. Skin biopsies for routine histology, direct immunofluorescence and immunohistochemical examination were taken. Methods: Skin biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence, indirect immunofluorescence and immunohistochemistry studies were performed. Results: Examination of the tissue sections demonstrated an inflammatory process involving capillaries and small blood vessels within the dermis and panniculitic adipose tissue. Focal extravasation of red blood cells into the dermal interstitial tissue was also observed. A mild, focal, lobular panniculitis was also present. Direct immunofluorescence and immunohistochemistry demonstrated deposits of several antibodies on vessels throughout the dermis. In addition, anti-neutrophilic cytoplasmic antibodies and neutrophil extracellular traps were identified. Conclusions: Few vasculitic processes have pathognomonic histologic findings. Often, the dermatopathologist and clinician must work together, combining clinical, histologic and other laboratory data to determine the nature of the primary disease process. In our case, a diagnosis of vasculitis with autoimmune overlapping auoimmune syndromes represented the consensus diagnostic conclusion.